2018
DOI: 10.1055/a-0755-2695
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Anti-Rubella Antibodies in Pregnant Women of Turkey, Results of 94508 Patients in a Tertiary Referral Center

Abstract: Aim To determine the seroprevalence of rubella in a tertiary referral center inAnkara,Turkey. Materials and methods A retrospective, cross-sectional study was performed from 2008 to 2017 at the outpatient clinic of Zekai Tahir Burak Women Health Care, Training and Research Hospital in Ankara, Turkey. The study included 94508 pregnant women and the patients were evaluated in terms of IgG and IgM status, IgG avidity and amniotic fluid PCR testing if needed. Results Seropositivity for anti-rubella IgG and IgM wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…In our country, IgG positivity is between 86.5-99.3% and IgM positivity varies between 0-3.2% (Table II) (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29). In a study conducted with 94508 pregnant women in Ankara province between 2008 and 2017, 89% seropositivity rates were found for Rubella IgG and IgM positivity was reported as 0.19% (35). In our study, the vaccination status of pregnant women was unknown, but seropositivity was found to be 90.7% and IgM positivity was found as 0.92%.…”
Section: Discussionmentioning
confidence: 70%
“…In our country, IgG positivity is between 86.5-99.3% and IgM positivity varies between 0-3.2% (Table II) (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29). In a study conducted with 94508 pregnant women in Ankara province between 2008 and 2017, 89% seropositivity rates were found for Rubella IgG and IgM positivity was reported as 0.19% (35). In our study, the vaccination status of pregnant women was unknown, but seropositivity was found to be 90.7% and IgM positivity was found as 0.92%.…”
Section: Discussionmentioning
confidence: 70%
“…Although there have been no large-scale studies of the association between rubella vaccination and social background, several studies have investigated the association between seroprevalence of rubella antibodies and social background (8,9). Previous studies have reported an association between rubella seroprevalence and geographical region or country where the pregnant women were born or raised, reflecting the influence of rubella vaccination policy in each region (10)(11)(12)(13)(14)(15). In Japan, Hanaoka et al measured rubella antibodies in pregnant women; those results reported that 16.1% of pregnant women had a low level of rubella antibodies (1:16 or less) (16).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Rubella IgG and IgM it has been demonstrated rates were 94.87% and 0.783%, respectively for pregnant woman in the meta-analysis study in Turkey (15). A recent study in Turkey shows that seropositivity for anti-rubella IgG and IgM were 89 and 0.19%, respectively (16). In our study, we determined the Rubella IgG and IgM seropositivities in pregnant women as IgG 94.3% and IgM 0.7%, respectively.…”
Section: Discussionmentioning
confidence: 58%